The Solubility/Degradation Study of Organophosphoric Acid Extractants in Sulphuric Acid Media - Azam, MA; Alam, S; Khan, FI (Journal of Chemical Engineering, 2011)
In order to improve the efficiency of the extractant or to prevent the loss of the extractant during metal extraction process the degradation/solubility loss of different organophosphorus acidic extractant was investigated. The effects of acid concentration, extractant concentration, temperature, diluent concentration were examined. Also, the kinetic study at different temperature on extractant degradation/solubility was investigated. Two types of extractant candidates such as Cyanex 272 (bis-2, 4, 4-trimethylpentylphosphinic acid) and D2EHPA (Di-(2-ethylhexyl) phosphoric acid) were tested. Sulphuric acid (H2SO4) was used in this experiment as an aqueous medium. In this study the pattern or characteristics of extractant solubility /degradation was observed based on organic transfer to the aqueous phase. With regard to phosphorus (P) content in the aqueous phase measured by inductively coupled plasma spectroscopy (ICP) the degradation/ solubility of D2HEPA was more than that of Cyanex 272. Keywords hydrometallurgy; degradation; solubility; cyanex272; D2EHPA DOI: 10.3329/jce.v25i0.7235 Journal of Chemical Engineering, IEB Vol. ChE. 25, No. 1, December 2010 pp.18-21